SHP-2-Induced Activation of c-Myc Is Involved in PDGF-B-Regulated Cell Proliferation and Angiogenesis in RMECs - Ma, Jun; Tang, Wenyi; Gu, Ruiping; Hu, Fangyuan; Zhang, Lei; Wu, Jihong; Xu, Gezhi (Frontiers in Physiology, 2020)
Background: Aberrant neovascularization resulting from inappropriate angiogenic signalling is closely related to many diseases, such as cancer, cardiovascular disease and proliferative retinopathy. Although some factors involved in regulating pathogenic angiogenesis have been identified, the molecular mechanisms of proliferative retinopathy remain largely unknown. In the present study, we determined the role of PDGF-B, one of the HIF-1-responsive gene products, in cell proliferation and angiogenesis in retinal microvascular endothelial cells (RMECs) and explored its regulatory mechanism. Methods: CCK-8, BrdU incorporation, tube formation, cell migration and Western blot assays were used in our study. Results: Our results showed that PDGF-B promoted cell proliferation and angiogenesis by increasing the activity of SHP-2 in RMECs, which was attenuated by the inhibition of PDGFR (platelet-derived growth factor receptor) or SHP-2 knockdown. Moreover, activation of c-Myc was involved in the processes of PDGF-B/SHP-2-driven cell proliferation in RMECs. The promoting effects of PDGF-B/SHP-2 on c-Myc expression were mediated by the Erk pathway. Conclusions: These results indicate that PDGF-B facilitates cell proliferation and angiogenesis, at least in part, via the SHP-2/Erk/c-Myc pathway in RMECs, implying new potential treatment candidates for retinal microangiopathy.